ERAmerica: Status of ERA Ratification - Jane Wells:::::: (1976)
This February 25, 1976 ERAmerica report summarizes the status of Equal Rights Amendment ratification, noting that 34 of the required 38 states had ratified the ERA, with a deadline of March 22, 1979. It explains that attempts by Nebraska and Tennessee to rescind ratification are considered invalid by legal authorities and outlines the legislative situation in the remaining unratified states, where ratification was generally not expected in 1976. The report also lists 15 states that had adopted their own state Equal Rights Amendments. Overall, it provides a state-by-state update and reflects stalled momentum for ERA ratification at that time.